Commercial development of Trichoderma species for control of soil-borne vegetable diseases and their integration into standard crop management practices - Kirstin L McLean; John S Hunt; Alison Stewart (浙江大学学报. 农业与生命科学版)
A 10 year research programme at Lincoln University, investigating the use of Trichoderma species for biological control of soil-borne diseases of vegetable crops, has resulted in the development of two commercial products. Trichodry ™ 6S and Trichoflow™ 6S based upon Trichoderma hamatum isolate 6SR4, are used to control Sclerotinia lettuce drop disease. The Trichodry 6S product is formulated as a dry flake, which is incorporated into nursery seedling mix and the Trichoflow 6S is a wettable powder which is used as a top-up drench before planting. The treatment stimulates seedling establishment and vigour and protects the developing seedling from Sclerotinia minor infection after transplanting in the field. The second commercial product is Trichopel™ Ali 52. based upon Trichoderma atroviride isolate C52, which is used to control Sclerotium cepivorum, the causal agent of Allium white rot disease. The product is formulated as a granule and applied into the furrow at planting time. The fungus proliferates in the rhizosphere region and protects the growing seedling from pathogen attack by a combination of nutrient competition, antibiosis and mycoparasitism. The use of Trichopel Ali 52 under low to medium disease pressure in Pukekohe, the main vegetable growing region of New Zealand, gave a three fold cost benefit through yield increases in the 2003-2004 season. Current field development work involves the use of a wettable powder formulation of T. atroviride distributed via a T-tape irrigation system to target mid-season applications of the product to the onion roots. Both products perform well under low to moderate disease pressure but, when there is high disease pressure, an integrated programme is required to give satisfactory control. Current research is focused on gaining a greater understanding of the biotic and abiotic factors, which influence biocontrol activity under field conditions as a means to enhance integrated control approaches. For example, T. atroviride C52, when applied to the planting furrow, is compatible with procymidone, benomyl and captan but not thiram when applied as onion seed treatments. It is also compatible with the majority of other fungicides applied to the onion crop to protect against foliar diseases such as Botrytis and downy mildew. The product can be integrated with the use of the germination stimulant diallyl disulphide (DADS) as long as the Trichoderma product is applied at least two weeks after DADS application. The product is not compatible with the use of nitrogen fertilisers due to the sensitivity of the Trichoderma mycelium to high N, thus, care must be taken to separate fertilizer application from that of the biocontrol product Expansion of the range of crop diseases targeted by the biocontrol products is currently under investigation with promising results obtained against a number of Botrytis diseases.